PENGARUH CITA RASA DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA RUMAH MAKAN ASEP STROBERI CICALENGKA, KAB BANDUNG - Alviani Maulida; Deni Solihin (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the effect of taste and price on customer satisfaction at Asep Stroberi Restaurant, Cicalengka, Bandung Regency. The background of this research is based on fluctuations in the number of visitors and customer complaints regarding inconsistencies in taste and the suitability of prices with the portions received. This research employs a quantitative method with an explanatory approach. Data were collected through questionnaires distributed to 100 respondents selected using purposive sampling, with the sample size determined using the Slovin formula. Data analysis techniques include validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²), conducted using SPSS version 27. The results indicate that, partially, taste and price have a positive and significant effect on customer satisfaction. Simultaneously, taste and price also have a significant effect on customer satisfaction. The coefficient of determination (R²) of 0.620 indicates that 62% of customer satisfaction is influenced by taste and price, while the remaining 38% is affected by other factors outside this study. This research is expected to provide managerial insights for Asep Stroberi Restaurant in improving taste quality and pricing strategies to enhance customer satisfaction sustainably